2013
DOI: 10.1007/978-1-4614-8603-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, Culture, and Cultural Analysis: Continuing Challenges

Abstract: Recent research indicates that asthma is more complicated than already recognized, requiring a multilateral approach of study in order to better understand its many facets. Apart from being a health problem, asthma is seen as a knowledge problem, and as we argue here, a cultural problem. Employing cultural analysis we outline ways to challenge conventional ideas and practices about asthma by considering how culture shapes asthma experience, diagnosis, management, research, and politics. Finally, we discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The simplistic approach of tailoring cultural interventions solely through adaptations such as language modifications of resources 12–14 is challenged by the findings of this study, which reinforce that culture and self‐management should not be treated as static 6–8 . South Asians are not a homogeneous cultural group, but nurture distinct intergenerational strategies for asthma self‐management, with adaptation through processes such as acculturation, illustrating that self‐management needs to be socio‐culturally and contextually relevant 8,9,44 . Integration promotes bi‐cultural competences and identities, including a good grasp of English, meaning that we found that participants tended to learn, negotiate and experiment with and/or fuse self‐management strategies from different sources (traditional culture, other cultures and religion) 18,19,45 .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The simplistic approach of tailoring cultural interventions solely through adaptations such as language modifications of resources 12–14 is challenged by the findings of this study, which reinforce that culture and self‐management should not be treated as static 6–8 . South Asians are not a homogeneous cultural group, but nurture distinct intergenerational strategies for asthma self‐management, with adaptation through processes such as acculturation, illustrating that self‐management needs to be socio‐culturally and contextually relevant 8,9,44 . Integration promotes bi‐cultural competences and identities, including a good grasp of English, meaning that we found that participants tended to learn, negotiate and experiment with and/or fuse self‐management strategies from different sources (traditional culture, other cultures and religion) 18,19,45 .…”
Section: Discussionmentioning
confidence: 79%
“… 6 , 7 , 8 South Asians are not a homogeneous cultural group, but nurture distinct intergenerational strategies for asthma self‐management, with adaptation through processes such as acculturation, illustrating that self‐management needs to be socio‐culturally and contextually relevant. 8 , 9 , 44 Integration promotes bi‐cultural competences and identities, including a good grasp of English, meaning that we found that participants tended to learn, negotiate and experiment with and/or fuse self‐management strategies from different sources (traditional culture, other cultures and religion). 18 , 19 , 45 What constitutes good self‐management is continually defined, agreeing with previous studies with different communities that gave precedence to religious self‐management over traditional cultural strategies, including African Americans, 46 American Indians 47 and South Asians.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Fortun et al . [24] recommended explanatory pluralism in tackling the ‘complex dynamics’ of asthma, as ‘modern biomedical culture expects pluralities to be reduced, “mysteries” to be cleared up, with straightforward and preferably singular explanations, after sufficient rational effort has been expended’ (p. 330). They highlight Tim Brookes' [25] autobiographical account of asthma as he searched for the cause of his illness, feeling that ‘this was what was needed to care for, if not cure, himself’ [25, p. 326].…”
Section: An Argument For Explanatory Pluralismmentioning
confidence: 99%